Unraveling astrocyte behavior in the space brain: Radiation response of primary astrocytes - Roggan, Marie Denise; Kronenberg, Jessica; Wollert, Esther; Hoffmann, Sven; Nisar, Hasan; Konda, Bikash; Diegeler, Sebastian; Liemersdorf, Christian; Hellweg, Christine E. (Frontiers in Public Health, 2023)
Introduction Exposure to space conditions during crewed long-term exploration missions can cause several health risks for astronauts. Space radiation, isolation and microgravity are major limiting factors. The role of astrocytes in cognitive disturbances by space radiation is unknown. Astrocytes' response toward low linear energy transfer (LET) X-rays and high-LET carbon (12C) and iron (56Fe) ions was compared to reveal possible effects of space-relevant high-LET radiation. Since astronauts are exposed to ionizing radiation and microgravity during space missions, the effect of simulated microgravity on DNA damage induction and repair was investigated. Methods Primary murine cortical astrocytes were irradiated with different doses of X-rays, 12C and 56Fe ions at the heavy ion accelerator GSI. DNA damage and repair (γH2AX, 53BP1), cell proliferation (Ki-67), astrocytes' reactivity (GFAP) and NF-κB pathway activation (p65) were analyzed by immunofluorescence microscopy. Cell cycle progression was investigated by flow cytometry of DNA content. Gene expression changes after exposure to X- rays were investigated by mRNA-sequencing. RT-qPCR for several genes of interest was performed with RNA from X-rays- and heavy-ion-irradiated astrocytes: Cdkn1a, Cdkn2a, Gfap, Tnf, Il1β, Il6, and Tgfβ1. Levels of the pro inflammatory cytokine IL-6 were determined using ELISA. DNA damage response was investigated after exposure to X-rays followed by incubation on a 2D clinostat to simulate the conditions of microgravity. Results Astrocytes showed distinct responses toward the three different radiation qualities. Induction of radiation-induced DNA double strand breaks (DSBs) and the respective repair was dose-, LET- and time-dependent. Simulated microgravity had no significant influence on DNA DSB repair. Proliferation and cell cycle progression was not affected by radiation qualities examined in this study. Astrocytes expressed IL-6 and GFAP with constitutive NF-κB activity independent of radiation exposure. mRNA sequencing of X-irradiated astrocytes revealed downregulation of 66 genes involved in DNA damage response and repair, mitosis, proliferation and cell cycle regulation. Discussion In conclusion, primary murine astrocytes are DNA repair proficient irrespective of radiation quality. Only minor gene expression changes were observed after X-ray exposure and reactivity was not induced. Co-culture of astrocytes with microglial cells, brain organoids or organotypic brain slice culture experiments might reveal whether astrocytes show a more pronounced radiation response in more complex network architectures in the presence of other neuronal cell types.